(untitled) (Revista Contexto & Educação, 2024)
The role of the social educator in promoting education in non-school spaces is multifaceted and fundamental for the holistic development of the individuals and communities they serve. Therefore, the objective of this study is to discuss the role of the social educator in promoting education in non-school spaces. Through a systematic literature review, studies discussing the importance of education in non-formal and informal spaces, the role of the social educator in knowledge construction, the connection with the reality of the learners, partnerships and collaborations with the third sector, as well as the challenges for this type of education, were analyzed. The results indicate that the work of the social educator is crucial for the promotion of quality, inclusive, and transformative education. Through innovative pedagogical practices, the social educator stimulates the autonomy and protagonism of the learners, promoting meaningful and contextualized learning. The proximity to the learners’ reality enables a more relevant education aligned with the needs and interests of the students. Moreover, building partnerships and collaborating with the third sector enhances the work of the social educator, expanding resources and strengthening educational actions. However, challenges such as lack of resources, social inequalities, and bureaucratic obstacles need to be addressed. To overcome these challenges, effective public policies, valuing education professionals, and strengthening partnerships among different actors are necessary. This study contributes to the appreciation of the social educator and highlights the importance of education in non-school spaces as a complementary alternative to formal education. Investing in the training and appreciation of these professionals, as well as in the creation of public policies that promote education in non-school spaces, is essential to foster a more just, equal, and educated society.